HUBUNGAN POLA ASUH ORANG TUA DAN PENERAPAN MANAJEMEN PENDIDIKAN ISLAMI TERHADAP KEPRIBADIAN SISWA - Suryani, Yenni (Al-aqidah | Jurnal Studi Islam, 2019)
The presence of parents is important for children and adolescents about change and identity seeking sometimes creates problems. Children?s needs are met if parents give good care. This study uses a quantitative correlational approach, in PGRI II Middle Depok and Al Falah Islamic Middle School Depok, Indonesia. The results of this study indicate the degree of closeness of the relationship between parenting (X1) and student personality (Y) indicated by the correlation coefficient (ry1) of 26.9%. Application of islamic education managements (X2) and student personality (Y) and the result (ry2) is 33.3%. the result of parenting and the application of management of Islamic education together with student personality, the level of correlation is quite strong as evidenced by variables (X1) and (X2) with students personality (Y) with a correlation coefficinet (ry12) of 27.9%.